Effect of Failure Fear and Achievement Motivation on Academic Procrastination Trough Self-Control - Rahmaningtyas, Wisudani; Widhiastuti, Ratieh; Farliana, Nina; Widiyastuti, Maulina (Dinamika Pendidikan, 2022)
The study aimed to analyze the effect of failure fear and achievement motivation on academic procrastination and to test the self-control variable as a mediating variable. This study used a quantitative approach. The research population was 997 students of the Faculty of Economics, Universitas Negeri Semarang in the class of 2019 and the sampling based on the Slovin formula was 286 students. The sampling technique used proportional random sampling. Data collection techniques used a questionnaire. The data analysis technique used descriptive statistical analysis and path analysis. The results showed that there was a positive and significant effect of failure fear on academic procrastination. Achievement motivation and self-control had no effect on academic procrastination. Partially, failure fear had no effect on self-control. Partially, achievement motivation had a positive and significant effect on self-control, and self-control was unable to mediate the effect of failure fear and achievement motivation on academic procrastination. Suggestions given from this study include that students are advised to reduce the habit of behaving in academic procrastination starting from the smallest things, and improve their self-control skills so they can behave positively and can make the right decisions.